Assessment of Etravirine Resistance in HIV-1-Infected Paediatric Patients using Population and Deep Sequencing: Final Results of the PIANO Study. Issue 4 (May 2016) - Tambuyzer, Lotke; Thys, Kim; Hoogstoel, Annemie; Nijs, Steven; Tomaka, Frank; Opsomer, Magda; Meyer, Sandra De; Vingerhoets, Johan
Background: We assessed etravirine resistance in treatment-experienced, HIV-1-infected children ( n =41)/adolescents ( n =60) who received twice-daily etravirine 5.2 mg/kg and a background regimen (boosted protease inhibitor plus nucleoside/nucleotide reverse transcriptase inhibitors, optional enfuvirtide/raltegravir) in a Phase II, open-label, multicentre trial (PIANO). Methods: In addition to phenotypes, viral genotypes were assessed by population and deep sequencing (PS and DS) in virological failures (VFs; baseline and end point) and responders (baseline). Minority resistance-associated mutations (RAMs) were defined as those with frequencies above 1% and not detected with PS. Results: By week 48, 41/101 (40.6%) patients experienced VF; 17/41 (41.5%) VFs and 22/54 (40.8%) responders had ≥1 baseline etravirine RAM by PS, mainly A98G, K101E, V106I and G190A. Baseline minority etravirine RAMs ( n ) were detected in 8/40 VFs (V90I [2], A98G [1], L100I [1], V106I [1], E138G [1] and Y181C [2]) and 5/38 responders (V90I [3], A98G [1], V106I [1] and E138G [1]). The most frequent emerging non-nucleoside reverse transcriptase inhibitor RAMs detected by PS (≥3 VFs; n ) were the etravirine RAMs Y181C (8), V90I (3), L100I (3) and E138A (3). In 15 of 29 (51.7%) VFs with baseline DS/PS and end point PS data, ≥1 emerging etravirine RAM was detected by PS, which was not detected at baseline by DS in most cases (12/15 [80.0%]). In 10/26 (38.5%) VFs with baseline/end point DS data, ≥1 additional emerging minority etravirine RAM was detected. Conclusions: Patterns of etravirine resistance in adults, adolescents and children experiencing VF are similar. The presence of minority etravirine RAMs at baseline was not consistently associated with treatment failure. ClinicalTrials.gov: NCT00665847.